HUBUNGAN USIA DAN PARITAS DENGAN KEJADIAN RETENSIO PLASENTA PADA IBU BERSALIN - ., Khotijah; Anasari, Tri; Khotijah, Amik (Bidan Prada: Jurnal Publikasi Kebidanan Akbid YLPP Purwokerto, 2014)
Retencio placenta is one of the causes of bleeding in the mother's birth. Retencio placenta to be influenced by maternal age and maternal parity. Age can be at risk of retencio placenta is less than 20 years and more than 35 years. While the parity that can be at risk of retencio placenta is grandemultigravida. To analyze an association between age and parity with the incidence of retencio placenta to mother in labor in hospitals of Banjarnegara in 2011. This study was an observational research with case control design. The population of study were all mothers in labor that experiencing retencio placenta and normal mothers in labor in Hospital of Banjarnegara in 2011. Research instrument used the observation sheet. The methods of data analysis used Chi Square test. The age of mothers in labor in hospitals Banjarnegara in 2011 mostly at aren’t risk as many as 124 people (67,4%).The parity of mothers in labor in hospitals of Banjarnegara in 2011 mostly at aren’t risk as many as 172 people (93.5%). There was an association between the age of the incidence of retencio placenta to mother in labor in hospitals of Banjarnegara in 2011 (p = 0,028). There was an association between parity with the incidence of retencio placenta to mother in labor hospitals Banjarnegara Year 2011 (p = 0.017). There was an association between age and parity with the incidence of retencio placenta to mother in labor in Banjarnegara hospitals in 2011. Midwives should to do the management of retencio placenta to mother in labor accordance with procedures established by the hospital with a full order can be handled maternal safely.. Keywords : age, parity, retencio placenta